2022
DOI: 10.33087/jiubj.v22i1.1927
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Berhubungan dengan Kejadian Bayi Berat Lahir Rendah (BBLR) di Rumah Sakit Muhammadiyah Palembang Tahun 2020

Abstract: Low birth weight baby is new born babies with weight < 2500 grams. The causative factors are chronic energy deficiency, anemia, preeclampsia, premature rupture of membranes, parity, birth spacing, gestational age, maternal age, maternal bad habits, and fetal factors. The purpose of this research is to know the relationship between parity, gestational age, hemoglobin level, and preeclampsia with the incidence of low birth weight babies in Muhammadiyah Hospital Palembang 2020. The method used in this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
0
0
3
Order By: Relevance
“…Obtained a p-value = 0.000 and it can be concluded that there is a significant relationship between preeclampsia and LBW due to the p-value (0.000 <0.05) (Oktarina et al, 2021). The P value = 0.000 concluded that there was a relationship between preeclampsia and the incidence of low birth weight babies at the Palembang Muhammadiyah Hospital (Budiarti et al, 2022). Chi-square statistical test with p-value = 0.000 shows that there is a significant relationship between preeclampsia and the incidence of LBW at the Regional General Hospital Raden Mattaher Jambi with an OR value of 3.496 (Primadevi & Susanti, 2022).…”
Section: Relationship Between Preeclampsia and Low Birth Weight At Pk...mentioning
confidence: 94%
“…Obtained a p-value = 0.000 and it can be concluded that there is a significant relationship between preeclampsia and LBW due to the p-value (0.000 <0.05) (Oktarina et al, 2021). The P value = 0.000 concluded that there was a relationship between preeclampsia and the incidence of low birth weight babies at the Palembang Muhammadiyah Hospital (Budiarti et al, 2022). Chi-square statistical test with p-value = 0.000 shows that there is a significant relationship between preeclampsia and the incidence of LBW at the Regional General Hospital Raden Mattaher Jambi with an OR value of 3.496 (Primadevi & Susanti, 2022).…”
Section: Relationship Between Preeclampsia and Low Birth Weight At Pk...mentioning
confidence: 94%
“…Bayi berat lahir rendah (BBLR) adalah bayi dengan berat lahir kurang dari 2.500 gram tanpa memandang masa gestasi (Ismayanah et al, 2020). BBLR tidak hanya dapat terjadi pada bayi prematur, tapi juga pada bayi cukup bulan yang mengalami hambatan pertumbuhan selama kehamilan (Budiarti et al, 2022) Jumlah angka kejadian BBLR yang tinggi dan dampak terhadap kematian bayi yang besar, memerlukan upaya penanggulangan dan pencegahan (Sadarang, 2021). Hal ini dapat dimulai dari mempersiapkan kondisi ibu yang sehat, serta dapat menjalani proses kehamilan dan persalinan dengan aman.…”
Section: Pendahuluanunclassified
“…Penelitian ini didukung oleh penelitian Yulianti (2021), yang mendapatkan hasil penelitian didapatkan angka uji statistik dengan menggunakan Chi Square tidak ada hubungan antara preeklampsia dengan kejadian bayi berat lahir rendah. Menurut Yulianti (2021) bahwa faktor yang berhubungan dengan kejadian BBLR adalah umur dan paritas (Yulianti, 2021).…”
Section: Sumber: Data Sekunderunclassified